Pengelolaan Administrasi Terhadap Arus Kas di PT Kimia Farma Trading & Distributor Bandung - Yulianti, Sania; Novita, Lola (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2024)
This study aims to assess the impact of administrative management on cash flow at PT Kimia Farma Trading & Distributor Bandung. During the internship program, the author was involved in various administrative tasks within the General Affairs division, including managing tax invoices, inputting operational cost data, and summarizing drug liabilities. The findings indicate that effective administrative management is crucial for ensuring smooth cash flow within the company. Delays in customer payments, often due to external factors, negatively affect the company’s liquidity and hinder its ability to meet financial obligations and invest in new projects. To address these challenges, several strategies can be implemented, such as enhancing administrative efficiency through the use of technology, tightening receivables management, and diversifying funding sources. The study concludes that optimizing administrative management with technological support can significantly improve the company’s financial performance and ensure long-term financial stability.